2016
DOI: 10.1080/10495398.2016.1178138
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Expression ofSFRP5in Tibetan Chicken and its Relationship with IMF Deposition

Abstract: Secreted frizzled related protein 5 (SFRP5), an anti-inflammatory adipokine, is relevant to the adipocyte differentiation. In order to clarify its role in regulating intramuscular fat (IMF) deposition in Tibetan chicken, the full-length sequence of the Tibetan chicken SFRP5 gene was cloned. The relative expression of SFRP5 gene was detected using quantitative RT-PCR in various tissues of 154 days old Tibetan chicken, as well as in breast muscle, thigh muscle, and adipose tissue at different growth stages. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Reports have revealed that SFRP5 initially binds with Wnt5a to prevent JNK activation in the downstream of Wnt signaling pathway in adipose tissues. As a result, we discovered a subsequent decrease in the production of pro-inflammatory cytokines, and antagonization of the IRS-1 Ser 307 phosphorylation [ 23 ]. Thus, SFRP5 has the ability to modulate the progression of T2DM as a result of its insulin-sensitizing and anti-inflammatory properties which have all been well documented [ 24 ].…”
Section: The Concept Of the Wnt Antagonist Sfrp5mentioning
confidence: 99%
See 1 more Smart Citation
“…Reports have revealed that SFRP5 initially binds with Wnt5a to prevent JNK activation in the downstream of Wnt signaling pathway in adipose tissues. As a result, we discovered a subsequent decrease in the production of pro-inflammatory cytokines, and antagonization of the IRS-1 Ser 307 phosphorylation [ 23 ]. Thus, SFRP5 has the ability to modulate the progression of T2DM as a result of its insulin-sensitizing and anti-inflammatory properties which have all been well documented [ 24 ].…”
Section: The Concept Of the Wnt Antagonist Sfrp5mentioning
confidence: 99%
“…The protective role of SFRP5 in the development of T2DM has been determined by findings that showed increased insulin sensitivity, decreased macrophage infiltration, and pro-inflammatory protein production [ 59 ]. The expression and transcription of SFRP5 have been reported to share a negative association with insulin resistance [ 23 ]. A reduction in SFRP5 transcription could result in an increase in the ratio of Wnt5a to SFRP5, which is correlated with inhibited glucose and insulin signaling [ 44 ].…”
Section: Sfrp5 and Insulin Resistance In T2dmmentioning
confidence: 99%
“…However, WGCNA, being considered as a correlation analysis, cannot solve all problems, but needs to combine other appropriate methods. (Li et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Asthma is a complex disease with diverse underlying pathological mechanisms with both the young and the elderly (Hasegawa et al, 2017;Li et al, 2016;Lotvall et al, 2011). Bronchial hyperresponsiveness, airway remodeling (Movassagh et al, 2016), abnormal hormone secretion (Newton et al, 2017), and chronic airway inflammation (Parulekar, Diamant & Hanania, 2017) are some of the major clinical features of asthma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation